Reporting sexual assault: a social ecology perspective - Ménard, Kim (Criminal justice recent scholarship, 2005)
Sexual assault prevalence and reporting -- Explaining victims' decision to contact the police -- Normative advice for labeling and reporting crime -- Sexual assault victims' decision to contact the police -- General discussion and policy implications.